2021
DOI: 10.1002/smll.202104229
|View full text |Cite|
|
Sign up to set email alerts
|

All‐in‐One: Multifunctional Hydrogel Accelerates Oxidative Diabetic Wound Healing through Timed‐Release of Exosome and Fibroblast Growth Factor

Abstract: The treatment of diabetic wounds remains a major challenge in clinical practice, with chronic wounds characterized by multiple drug-resistant bacterial infections, angiopathy, and oxidative damage to the microenvironment. Herein, a novel in situ injectable HA@MnO 2 /FGF-2/Exos hydrogel is introduced for improving diabetic wound healing. Through a simple local injection, this hydrogel is able to form a protective barrier covering the wound, providing rapid hemostasis and long-term antibacterial protection. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
125
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 208 publications
(126 citation statements)
references
References 52 publications
0
125
0
1
Order By: Relevance
“…From a therapeutic perspective, previous studies have pointed out that the self-levitating nanofiber gel-encapsulated polydeoxyribonucleotide benefits chronic ulcer in diabetic rats (Chen et al, 2016). The research of Xiong Y et al indicates that chronic diabetic wound repair benefits from the nanohydrogel material loaded with growth factors (Xiong et al, 2021). At present, clinical trials have confirmed that miRNA is a key regulatory molecule of fracture healing and is likely to be a pathway to promote normal physiologic fracture healing.…”
Section: Discussionmentioning
confidence: 98%
“…From a therapeutic perspective, previous studies have pointed out that the self-levitating nanofiber gel-encapsulated polydeoxyribonucleotide benefits chronic ulcer in diabetic rats (Chen et al, 2016). The research of Xiong Y et al indicates that chronic diabetic wound repair benefits from the nanohydrogel material loaded with growth factors (Xiong et al, 2021). At present, clinical trials have confirmed that miRNA is a key regulatory molecule of fracture healing and is likely to be a pathway to promote normal physiologic fracture healing.…”
Section: Discussionmentioning
confidence: 98%
“…Through a continuous supply of O 2 and timed release of ExosM2@miR-223 and FGF-2, the HA@MnO2/FGF-2/Exos hydrogel creates an appropriate immune microenvironment to improve the healing of DW in vivo. 137 Although the application of traditional biomaterials and wound dressings contributes to an effective wound healing outcome, DW repair is a dynamic and complex process. Excessive inhibition of wound inflammation is harmful.…”
Section: Targeted Immunotherapy For Dwmentioning
confidence: 99%
“…Adding bioactive substances that can deliver oxygen to the hydrogel can effectively improve the hypoxic microenvironment of the skin and promote vascular regeneration. For example, spirulina can release oxygen (Figure 2H) 57 under laser irradiation; NOX powder can deliver dissolved oxygen to the wound site; 25 oxygen microsphere oxygen‐release microsphere can maintain oxygen release for at least 2 weeks; 26 manganese dioxide (MnO 2 ) nanosheets can induce the decomposition of endogenous ROS (H 2 O 2 ) into oxygen (O 2 ) 27 . Proanthocyanidin B2, 28 cinnamaldehyde, 29 tannic acid, 30 polydopamine nanoparticles, 31 epigallocatechin gallate (EGCG), 32 and hydrogel dressings have significant free radical scavenging and antioxidant properties, which can remove ROS produced in hypoxic wounds and inhibit excessive inflammation and promote wound angiogenesis.…”
Section: Application Of Biomaterials In Tissue Engineering Vasculariz...mentioning
confidence: 99%